Nature Driven Urbanism. - (:unkn) unknown (Springer, 2020)
The book discusses the way that a nature-driven approach to urbanism can be applied at each of the urban scales; architectural design, urban design of neighborhoods, city planning and landscape architecture, and at the city and regional scales. At all levels nature-driven approaches to design and planning add to the quality of the built structure and furthermore to the quality of life experienced by people living in these environments. To include nature and greening to built structures is a good starting point and can add much value. The chapter authors have fiducia in giving nature a fundamental role as an integrated network in city design, or to make nature the entrance point of the design process, and base the design on the needs and qualities of nature itself. The highest existence of nature is a permanent ecosystem which endures stressors and circumstances for a prolonged period. In an urban context this is not always possible and temporality is an interesting concept explored when nature is not a permanent feature. The ecological contribution to the environment, and indirect dispersion of species, from a temporary location will, overall add biodiversity to the entire system.
Keywords: Stadtplanung; Stadtnatur; Stadtgrün; Brache; Stadtbegrünung; Klimawandel; Stadtökologie; Dürre; Überschwemmungsgebiet; Hochwasserschutz; Flusslauf; Uferbereich; Verkehrsweg; Umweltverträglichkeit; Grüne Infrastruktur; Unbebautes Land